DNA methylation in cancer - Vertino, Paula (Henry Stewart Talks, 2011)
DNA methylation in cancer, Overview of DNA methylation in human cells, Relationshoip of DNA methylation and chromatin structure, Contribution of hypo/hypermethylation to tumorigenesis, Mechanisms underlying altered DNA methylation patterns in cancer, miRNAs as effectors and targets of aberrant DNA methylation in cancer, Cancer methylation biomarkers, Reversing DNA methylation in cancer therapy